2015
DOI: 10.1109/tbme.2015.2421296
|View full text |Cite
|
Sign up to set email alerts
|

Local Gradients in Electrotonic Loading Modulate the Local Effective Refractory Period: Implications for Arrhythmogenesis in the Infarct Border Zone

Abstract: Ectopic electrical activity that originates in the peri-infarct region can give rise to potentially lethal re-entrant arrhythmias. The spatial variation in electrotonic loading that results from structural remodelling in the infarct border zone may increase the probability that focal activity will trigger electrical capture, but this has not previously been investigated systematically. This study uses in-silico experiments to examine the structural modulation of effective refractory period on ectopic beat capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…How the Cx43-dependent myofibroblast dynamism characterized in our study affects the formation of proarrhythmic substrates at the heterocellular coupling area should be investigated further. The irregularity of the interface between surviving cardiac muscle and the scar tissue of myocardial infarction is a well-characterized determinant and originator of re-entrant arrhythmias (60,61). Modeling studies have shown that microstructural variations in cardiac tissue facilitate the formation of isolated sites of wavefront breakthrough that may enable abnormal electrical activity; these small regions of heterogeneous diseased tissue can develop more widespread re-entrant activity (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…How the Cx43-dependent myofibroblast dynamism characterized in our study affects the formation of proarrhythmic substrates at the heterocellular coupling area should be investigated further. The irregularity of the interface between surviving cardiac muscle and the scar tissue of myocardial infarction is a well-characterized determinant and originator of re-entrant arrhythmias (60,61). Modeling studies have shown that microstructural variations in cardiac tissue facilitate the formation of isolated sites of wavefront breakthrough that may enable abnormal electrical activity; these small regions of heterogeneous diseased tissue can develop more widespread re-entrant activity (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…Such electrotonic effect can be seen in Figure 6. PVCs originated everywhere throughout the isthmus, but were found to lie away from both proximal and distal mouths (minimum focus-to-mouth distance was 2.61 mm for w isth = 0.2 mm) due to unfavored loading conditions in regions of abrupt tissue expansion [36,37]. As the size of the isthmus increases, the electrotonic load on cells comes closer to that of a well-coupled 2D cardiac tissue.…”
Section: The Role Of Electrotonic Loadmentioning
confidence: 99%
“…The cardiac safety factor for propagation has been shown to be minimum near regions of thin-to-thick tissue expansion [36], such as the mouth of the isthmus, where source current generated by the excited cells is insufficient to activate the downstream tissue [37]. Sink effects at the mouth of the isthmus can also be altered by elevations in V m resulting from subthreshold DADs [17].…”
Section: The Role Of Electrotonic Loadmentioning
confidence: 99%
“…We have recently demonstrated [5,6] that changes in local electrotonic loading (due to the presence of tissue boundaries, small cavities and rapid tissue expansions), can significantly affect the excitability of cardiac tissue, causing a corresponding spatial variation in local effective refractory period (ERP). Such spatial gradients in ERP were witnessed in absence of any significant changes in action potential duration (APD), and were shown to be responsible for causing uni-directional block and subsequent arrhythmia induction.…”
Section: Introductionmentioning
confidence: 99%
“…Such gradients are present both when the initial wavefront (prior to ERP calculation) occurs from healthy-to-BZ as well as from BZto-healthy tissue. In our previous studies [5,6], we have demonstrated how gradients in ERP (caused in these cases due to differences in electrotonic loading brought about by structural heterogeneity) can facilitate uni-directional conduction block following a focal ectopic beat applied close to the ERP of tissue experiencing a high gradient. We suggest that a similar mechanism may occur in this scenario.…”
mentioning
confidence: 98%